Comparative Analysis of Activity-Based Costing and Traditional Methods in Determining Basic Room Rates in Didu's Homestay Banyuwangi - Firda Rachma Amalia; Ayu Wanda Febrian (Universitas Airlangga, 2022)
Determining competitive price is one of the ways to win in a market. The rate can be concluded by accurately calculating fixed and variable costs incurred in a business. However, regarding determining room costs, many homestay businesses do not apply proper calculation techniques. Their price often does not reflect specific activities, as many cost categories are indirect and fixed. This study compares the basic rate for homestay room business using traditional, and activity-based costing (ABC) approaches. Activity-based costing can allocate activity costs appropriately based on the consumption of each activity. This study collected data through observation and interviews at a homestay, additionally commanded a descriptive analysis. The data source was obtained from internal data, namely, financial data obtained from the homestay. There were three stages of data analysis, i.e. (1) calculation of the cost of renting the room using the traditional method; (2) calculation of the cost of rent for rooms using the ABC system; (3) comparison study between the calculation of the cost of rent for the room currently used by the homestay with calculations using the traditional method and the ABC System.